2016
DOI: 10.1021/acsbiomaterials.6b00071
|View full text |Cite
|
Sign up to set email alerts
|

Microsphere-Based Osteochondral Scaffolds Carrying Opposing Gradients Of Decellularized Cartilage And Demineralized Bone Matrix

Abstract: Extracellular matrix (ECM) "raw materials" such as demineralized bone matrix (DBM) and cartilage matrix have emerged as leading scaffolding materials for osteochondral regeneration owing to their capacity to facilitate progenitor/resident cell recruitment, infiltration, and differentiation without adding growth factors. Scaffolds comprising synthetic polymers are sturdy yet generally lack cues for guiding cell differentiation. We hypothesized that opposing gradients of decellularized cartilage (DCC) and DBM in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…While these studies demonstrated that PLL treatment was well tolerated by cells [55,62,63,67], a critical objective of the current investigation was to verify that lentivirus immobilization did not negatively impact the native structure or composition of CDM, which in turn influence cell attachment and viability. Minimizing alterations to CDM is of the utmost importance as processing techniques including excessive chemical crosslinking [47,68], pepsin digestion [34,69], encapsulation in PLGA microspheres [23,70], incorporation with carbon nanotubes [71], or functionalization with methacrylate groups [17,72] can inhibit cell attachment [47,68,71] and compromise the ability of CDM to support chondrogenesis [47,[68][69][70] or endochondral ossification [17]. In the current study, there was no difference in the baseline biochemical composition between NT and eGFP-transduced constructs (reported in the caption of Fig.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…While these studies demonstrated that PLL treatment was well tolerated by cells [55,62,63,67], a critical objective of the current investigation was to verify that lentivirus immobilization did not negatively impact the native structure or composition of CDM, which in turn influence cell attachment and viability. Minimizing alterations to CDM is of the utmost importance as processing techniques including excessive chemical crosslinking [47,68], pepsin digestion [34,69], encapsulation in PLGA microspheres [23,70], incorporation with carbon nanotubes [71], or functionalization with methacrylate groups [17,72] can inhibit cell attachment [47,68,71] and compromise the ability of CDM to support chondrogenesis [47,[68][69][70] or endochondral ossification [17]. In the current study, there was no difference in the baseline biochemical composition between NT and eGFP-transduced constructs (reported in the caption of Fig.…”
Section: Discussionmentioning
confidence: 51%
“…8A). In contrast with previous studies that incorporated CDM into biphasic constructs with the subchondral bone region composed of demineralized bone matrix [23,36,37], hydroxyapatite [100], calcium phosphate [44], or synthetic polymers [38], the current study generated both cartilaginous and osseous phases from a single, compositionally homogenous CDM substrate. Furthermore, the current study demonstrated that lentiviral transduction produced robust growth factor synthesis for the entire 50-day culture period, which did not peak until Day 16 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, scaffolds based on the assembly of µPs are versatile for a wide range of TE applications, from soft to hard tissues. For instance, the use of synthetic polymers resulted in high mechanical stiffness and a slow degradation rate for in vivo load-bearing implantation, such as bone [74] and osteochondral tissue [75]. Conversely, soft biopolymeric chitosan µPs scaffolds were proposed as a 3D, functional neuronal networks’ regeneration platform [76].…”
Section: Microparticles (µPs) As Building Blocks For Modular Tissumentioning
confidence: 99%
“…While synthetic scaffolds can offer highly tunable degradation properties, their degradation is often decoupled from cellular remodeling processes and instead is mediated by hydrolysis [3, 21, 22]. Overly rapid degradation can lead to premature loss of scaffold properties before mechanically competent tissue has formed, resulting in implant failure [23]. Conversely, the persistence of synthetic polymers beyond the remodeling process can induce a foreign body response [24] and fibrotic tissue deposition [3, 14, 25, 26], which inhibit subchondral bone remodeling [3, 14, 26] and cause osseous wall resorption and defect widening [6].…”
Section: Introductionmentioning
confidence: 99%